Characteristics of the pulsating flow and heat transfer in an elbow tailpipe of a self-excited Helmholtz pulse combustor. (5th September 2016) - Xu, Yanying; Zhai, Ming; Guo, Li; Dong, Peng; Chen, Jian; Wang, Zhi
Highlights: A valveless Helmholtz pulse combustor with an elbow tailpipe was designed. The pulsating flow in the elbow tailpipe was numerically simulated by FLUENT. The mean velocity decrease with the velocity amplitude along the tailpipe. The internal and external elbow pressure decrease along the tailpipe. Periodical vortex shapes and positions contribute to heat transfer enhancement. Abstract: A valveless self-excited Helmholtz pulse combustor with an elbow tailpipe was designed. The pressures along the tailpipe and the internal and external elbow section were measured. The pulsating flow in the elbow tailpipe was numerically simulated by FLUENT. Numerical simulation results show that the mean velocity decrease with the velocity amplitude along the tailpipe. The mean and amplitude of area-averaged pressure and internal and external elbow pressure decrease along the tailpipe. The mean and amplitude of the internal elbow pressure are less than those of the external elbow pressure. The simulation results are in good agreement with the experimental data. The mass-averaged velocity-reversing, Dean vortex forming, shedding and reforming process and periodical Dean vortex shapes and vortex core positions contribute to convective heat transfer enhancement.